How Junior High School English Teachers in Bengkulu City Utilise Published Textbooks in the Classroom: A Classroom Observation Study - Safnil Safnil (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
The purpose of the study was to find out: (1) how the junior high school English teachers in Bengkulu city exploited the commercially published textbooks for classroom use; (2) if there was a difference in the way the experienced and the inexperienced English language teachers exploited the commercially published textbooks in the classroom; and (3) whether the teachers adapted textbooks or produced their own materials for classroom use. Twelve English teachers (6 experienced and 6 inexperienced teachers) from four different junior high schools or SMPs (2 favourite and 2 non-favourite) in Bengkulu city were the participants in this study. Data were obtained through a questionnaire, classroom observations, and sample lesson plans. The results of the study revealed that: first, the junior high school English language teachers (ET and IT); (1) used the commercially prescribed textbooks to a large extent; (2) there was not much difference between the way experienced teachers and inexperienced teachers exploited the textbooks; (3) both groups of teachers adapted the textbooks or produced their own teaching materials.